PERSEPSI AUDITEE TERHADAP PELAKSANAAN FUNGSI SATUAN PENGAWAS INTERNAL UNIVERSITAS SEBELAS MARET SURAKARTA - Mahanani Abqory; Abdul Halim (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The research aims to deeply investigate auditee’s perception on the implementation of internal audit function to the Internal Supervisory Unit as theInternal Auditor at Sebelas Maret University viewed from its independence, competence, performance of audit, and added-value. The respondents of theresearch were auditees which were directly related to finance and asset management in UNS and were directly related to the Internal Supervisory Unit ininternal audit activity. The research is intended to give suggestions to the management about the evaluation of the internal audit activity through auditee’sperception which can help management to come to the decision to increase the quality of the Internal Supervisory Unit as the Internal Auditor of Sebelas Maret University.The result of the research shows that the auditee has good perception to the Internal Supervisory Unit function as the Internal Auditor of Sebelas Maret University, viewed from its independence, competence, performance of audit, and added-value. Although it has some shortages in terms of audit planning process, coverage of audit, and intensity of accompaniment to the auditee.